INTEGRASI MEDIA MNC GROUP DALAM MENINGKATKAN EFISIENSI DAN KOMPETISI DI PASAR BISNIS INDUSTRI MEDIA PENYIARAN - Geofakta Razali (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2019)
Jurnal ini memberikan pemahaman tentang integrase yang terjadi pada media khususnya MNC Group. Integrasi tersebut berhasil memberikan improvisasi pada efisiensi. Persaingan pasar industry media menjadi sebuat ketentuan yang menjadi landasan berpacunya media untuk menjadi sebuah holding dan saling menunjang dari sisi satu dan sisi lainnya. Penulis menggunakan teori SCP untuk melihat bagaimana struktur media, perilaku media, dan performancenya untuk mencapai sebuah konsep bisnis industry media yang sempurnaThis thesis analyzes MNC Media at the viewside of media group in Indonesia with through the time and had raced into the largest integration media group in Southeast Asia. To analyze the efficiency and the competition that created by MNC Media Group, actually, researchers try to analyze based on the theory. That theory is Industrial Organization owned media Kranenburg. This theory explains how Structure, Conduct and Performance of a media become into a value chain to survive in the competition group media today we called is integration. There is also a research concept by adding strategy concepts of business broadcast media industry. The indicator used to measure and analyze the success rate occurred partly based on data media with the large revenue increase profit margins, many advertisers, competition audience share, and the company's efficiency.Keywords: Integration, MNC Media Group, Efficiency, Competition, Industry Media Broadcasting Business